Strategic Leadership Competency Analysis of Lieutenant General TNI (Purn.) Mochamad Jasin in Maintaining National Security - Frely Rahmawati; Sri Sundari; Imam Supriyadi (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Indonesia is an independent country that has a long history of heroes fighting for the independence of their nation. One of them is TNI soldier Mochamad Jasin. Lieutenant General TNI (Purn.) Mochamad Jasin is a military figure who fought for the Indonesian people against various threats that threatened the security of the country and the comfort of the nation. During his service as a TNI soldier, many state assignments were given to him. Apart from working as an intellectual, he is also able to work as a soldier on the battlefield. He is a TNI soldier who has strategic leadership competencies. He always uses strategic thinking in carrying out the duties of the country he is carrying. The research method used is a descriptive qualitative method, which is described by an in-depth analysis of various reference sources with a literature study approach. The results of the study show that the strategic leadership possessed by Lieutenant General TNI (Purn.) Mochamad Jasin should be used as a reflection for TNI soldiers, especially regarding their understanding of the condition of the nation and territory of Indonesia, as well as their effective attitude and efficiency in utilizing state facilities to support their duties to maintain national security and defend state sovereignty from various threats, both military and non-military.